2015
DOI: 10.1142/s0217984915501973
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface-enhanced Raman scattering of InAs particles of subwavelength apertures at terahertz frequencies

Abstract: We present a theoretical mechanism for electric field enhancement with SERS of InAs particles of subwavelength apertures under THz excitation. The distribution of electric field confirms that there is a strong enhancement in the InAs particles at THz frequencies. The InAs with a Drude-like behavior in THz range, which is similar to metals at optical frequencies, leads to different SERS when the parameters of these two particles change. The SERS enhancement factor can reach [Formula: see text] under the certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, numerical simulations demonstrated that InAs antennas, formed by triangular or dot dimers, can exploit plasmons in the terahertz range to concentrate the electromagnetic field within the antenna gap, giving rise to exceptional enhancement (up to 10 11 ). 233 Other possibilities for SERS could be opened by direct exploitation of the strong internal fields originating from the efficient coupling of light with high-refractive-index InAs NWs. 234 In the case of sulfides and selenides, most published works have been related to the peculiarities resulting from their size reduction to form quantum-dot structures.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, numerical simulations demonstrated that InAs antennas, formed by triangular or dot dimers, can exploit plasmons in the terahertz range to concentrate the electromagnetic field within the antenna gap, giving rise to exceptional enhancement (up to 10 11 ). 233 Other possibilities for SERS could be opened by direct exploitation of the strong internal fields originating from the efficient coupling of light with high-refractive-index InAs NWs. 234 In the case of sulfides and selenides, most published works have been related to the peculiarities resulting from their size reduction to form quantum-dot structures.…”
Section: +mentioning
confidence: 99%
“…Another important future challenge is given by their possible exploitation for amplifying Raman in the terahertz spectral region. For example, numerical simulations demonstrated that InAs antennas, formed by triangular or dot dimers, can exploit plasmons in the terahertz range to concentrate the electromagnetic field within the antenna gap, giving rise to exceptional enhancement (up to 10 11 ) . Other possibilities for SERS could be opened by direct exploitation of the strong internal fields originating from the efficient coupling of light with high-refractive-index InAs NWs …”
Section: Sers-active Dielectricsmentioning
confidence: 99%